Immunotherapy Associated Neurotoxicity in Pediatric Oncology - Shalabi, Haneen; Nellan, Anandani; Shah, Nirali N.; Gust, Juliane (Frontiers in Oncology, 2022)
Novel immunotherapies are increasingly being employed in pediatric oncology, both in the upfront and relapsed/refractory settings. Through various mechanisms of action, engagement and activation of the immune system can cause both generalized and disease site-specific inflammation, leading to immune-related adverse events (irAEs). One of the most worrisome irAEs is that of neurotoxicity. This can present as a large spectrum of neurological toxicities, including confusion, aphasia, neuropathies, seizures, and/or death, with variable onset and severity. Earlier identification and treatment, generally with corticosteroids, remains the mainstay of neurotoxicity management to optimize patient outcomes. The pathophysiology of neurotoxicity varies across the different therapeutic strategies and remains to be elucidated in most cases. Furthermore, little is known about long-term neurologic sequelae. This review will focus on neurotoxicity seen with the most common immunotherapies used in pediatric oncology, including CAR T cell therapy, alternative forms of adoptive cell therapy, antibody therapies, immune checkpoint inhibitors, and tumor vaccines. Herein we will discuss the incidence, pathophysiology, symptomatology, diagnosis, and management strategies currently being utilized for immunotherapy-associated neurotoxicity with a focus on pediatric specific considerations.